Distance in the existence of political pathologies : rationalized transport policies and trade - Akyelken, N (Edward Elgar Publishing, 2011)
The sensitivity of international trade flows to distance is often examined through freight transport costs, although the inclusion of these costs in trade analysis is relatively new. Furthermore, it is seldom sufficiently sophisticated to account for the complexities involved in policy-making either by the authorities that provide transport infrastructure and regulate the system, or trade ministries that have wider responsibilities for such things as currency systems and factor mobility. This becomes more relevant as international agreements on climate change are gaining importance and are affecting transportation, and as individual nations are required to contribute to the meeting of global emissions targets. Early economic theory explaining international trade largely ignored transport costs, which was in contrast to economic geography models that put emphasis on spatial factors that eventually affect transport costs and, with them, migration and trade-flows. Economic geography has stressed the importance of economic and distance-related factors when explaining trade preferences, and the dispersion of industrial activity by recognizing that transport costs are one of the main determinants of trade and economic growth variations. As concerns about the environment are increasingly shaping national policies, there is a growing perception that more account needs to be taken of the unanticipated longer-term effects of negative environmental externalities on transport services and trade patterns. Furthermore, transport policies do not necessarily follow a ‘rational path’. Political pathologies1 in policy-making arise as a result of the deviations from socially optimum decisions. In other words, decision-makers do not necessarily take rational decisions